Approaching deliberative democracy: theory and practice - Cavalier, Robert (Carnegie Mellon Univ. Press, 2011)
Introduction : the conversational turn in political philosophy / Robert Cavalier -- James M. Buchanan, John Rawls, and democratic governance / S.M. Amadae -- From citizen to consumer and back again : deliberative democracy and the challenge of interdependence / Benjamin Barber -- Deliberation, but voting too / Gerry Mackie -- Learning democratic communication through "deliberative polling" / Christian List and Anne Sliwska -- The promises and challenges of deliberative democracy in practice : a comparative case study of two school districts / Julie Marsh -- Building trust through inclusion : reflections on the practice of deliberative democracy / Gregory J. Crowley -- Deliberative polling in Pennsylvania : from student senate to state senate / Michael Bridges and Joanna Dickert with Jayna Bonfini -- CItizens deliberating online : theory and some evidence / Vincent Price -- Deliberative e-democracy / Robert Cavalier